Cytotoxic Activity of Ethanolic Extract of Zanthoxylum acanthopodium DC. Fruit as Phytosomal System against MCF-7 Cell Line - Yohana Chaerunisaa, Anis; Muhaimin, Muhaimin; Nur Fatimah, Siti; Kusuma Dewi, Mayang; Amalia, Riezki; Fauziyah Sutisna, Siti (Trends in Sciences, 2025)
Zanthoxylum acanthopodium DC., known as andaliman, contains bioactive compounds with potential anticancer properties. This study investigated the cytotoxic activity of the ethanolic extract of Z. acanthopodium and its phytosomal formulation (Phytosome-EEA) against the MCF-7 breast cancer cell line. Phytosomes were prepared using antisolvent precipitation and optimized based on phospholipid ratios, reflux temperature, and n-hexane droplet rate. The phytosomes were characterized by particle size, polydispersity index, zeta potential, entrapment efficiency, stability tests, and morphology study by Transmittion Electron Microscopy (TEM). WST-1 assay at 450 nm was used to assess cytotoxicity against HEK 293A and MCF-7 cells, while apoptosis was evaluated using Annexin V-PI staining. The optimized phytosome formulation yielded nanoparticles with an average size of 192.4 nm, polydispersity index of 0.783, a zeta potential of −36.7 V, and an entrapment efficiency of 90.26%. When stored at 4, 25 and 40 °C for 14 days, there were no significant changes in particle size, zeta potential, or cytotoxicity, indicating high physical stability. Both the ethanolic extract and phytosomes exhibited cytotoxic activity against MCF-7 and HEK 293A cells, with IC₅₀ values of 100.2 and 109.2 µg/mL, respectively. The cell death induced by EEA occurred primarily via apoptosis, while Phytosome-EEA promoted increased late apoptosis. Although the selectivity index remained < 1, the phytosomal formulation maintained consistent cytotoxic activity and improved physicochemical characteristics compared to the crude extract. HIGHLIGHTS The ethanolic extract of acanthopodium fruit contains bioactive compounds such as alkaloids, flavonoids, and tannins that contribute to the anticancer effect. The phytosome formulation produced stable particles with a particle size of 192.4 nm, zeta potential of -33.2 mV, and high entrapment efficiency of 90.26%. The andaliman extract showed cytotoxic activity against breast cancer cells (MCF-7), but less selective (SI < 1). IC50 value against MCF-7: 100.2 µg/mL (moderately active category) Phytosome formulation did not improve selectivity, but provided good physical stability and was stable during storage. Phytosomes have potential as an herbal-based anticancer delivery system, but further optimization is needed. Further considerations such as targeting modifications are needed to be more selective towards cancer cells GRAPHICAL ABSTRACT